The Multidimensional Poverty Measure among Malaysian Employee Provident Fund (EPF) Retirees - Solaymani, Saeed; Vaghefi, Negin; Kari, Fatimah (Springer Verlag (Germany), 2019)
Assessing poverty using multiple dimensions of deprivation provides a comprehensive picture of poverty. No one factor, like income or any monetary-based indicator is uniquely able to capture all of the factors that contribute to poverty. This study attempts to evaluate the multidimensional poverty measure among Malaysian Employee Provident Fund (EPF) retirees by using Alkire and Foster multidimensional poverty index to a set of deprivation dimensions. The findings indicate that around 84% of EPF retirees were identified as multidimensionally poor, meaning that they are in acute poverty. On average, poor retirees are deprived of 48% of weighted indicators. The results also show that women are more multidimensionally poor compared to men in terms of transportation, income, home ownership and education. The study discovered that Indian retirees are more deprived than other ethnic groups, followed by Malays. In this regard, it is necessary to strengthen current retirement savings institutions to reduce the impacts of the retirement crisis. The government needs to provide a Social Security system that rolls back the decline of Malaysian’s retirement savings. © 2018, Springer Nature B.V. and The International Society for Quality-of-Life Studies (ISQOLS).